The Synergy between Bio-Aggregates and Industrial Waste in a Sustainable Cement Based Composite - Grădinaru, Cătălina Mihaela; Șerbănoiu, Adrian Alexandru; Muntean, Radu; Șerbănoiu, Bogdan Vasile (MDPI AG, 2021)
The effects of the fly ash and of the sunflower stalks and corn cobs within a cement-matrix composite were studied under the aspects of density, compressive strength, splitting tensile strength, elasticity modulus, and resistance to repeated freeze-thaw cycles. In the research were developed 20 recipes of cement-based composite, including the reference composite. Fly ash was used as partial cement replacement (10, 20 and 30% by volume), and the vegetal aggregates made by corn cobs and sunflower stalks as partial replacement of the mineral aggregates (25 and 50% by volume). The study results revealed that a lightweight composite can be obtained with 50% of vegetal aggregates, and the fly ash, no matter its percentage, enhanced the compressive strength and splitting tensile strength of the compositions with 50% of sunflower aggregates and the freeze-thaw resistance of all compositions with sunflower stalks.